First Photographic Evidence of the Central African Oyan in Uganda - Akampurira, Emmanuel; Uzabaho, Eustrate; Bitariho, Robert; Moore, Jennifer F. (African Journal of Ecology, 2024)
Arboreal camera trap photographs were captured of the Central African Oyan Poiana richardsonii in Bwindi Impenetrable National Park, Uganda. In total, 10 photographs were obtained from three sites in the park in 2019. This is likely the furthest east record of this species.
Keywords: Photographic Evidence; Central African; Uganda